An In Vitro and In Vivo Comparison of Osteogenic Differentiation of Human Mesenchymal Stromal/Stem Cells. (8th September 2021) - Mollentze, Jamie; Durandt, Chrisna; Pepper, Michael S.
Abstract : The use of stem cells in regenerative medicine, including tissue engineering and transplantation, has generated a great deal of enthusiasm. Mesenchymal stromal/stem cells (MSCs) can be isolated from various tissues, most commonly, bone marrow but more recently adipose tissue, dental pulp, and Wharton's jelly, to name a few. MSCs display varying phenotypic profiles and osteogenic differentiating capacity depending and their site of origin. MSCs have been successfully differentiated into osteoblasts both in vitro an in vivo but discrepancies exist when the two are compared: what happens in vitro does not necessarily happen in vivo, and it is therefore important to understand why these differences occur. The osteogenic process is a complex network of transcription factors, stimulators, inhibitors, proteins, etc., and in vivo experiments are helpful in evaluating the various aspects of this osteogenic process without distractions and confounding variables. With that in mind, the results of in vitro experiments need to be carefully considered and interpreted with caution as they do not perfectly replicate the conditions found within living organisms. This is where in vivo experiments help us better understand interactions that might occur in the osteogenic process that cannot be replicated in vitro . Potentially, these differences could also be exploited to develop an optimal MSC cell therapeutic product that can be used for bone disorders. There are many bone disorders, most of which cause a great deal of discomfort. Clinically acceptable protocols could be developed in which MSCs are used to aid in bone regeneration providing relief for patients with chronic pain. The aim of this review is to examine the differences between studies conducted in vitro and in vivo with regard to the osteogenic process to better define the gaps in current osteogenic research. By better understanding osteogenic differentiation, we can better define treatment strategies for various bone disorders.